IRRITANT CONTACT DERMATITIS ON HANDS AND DIAGNOSIS OF IT: A REVIEW - ALOTAIBI, ADEL MUTLAQ; AL-SULAIMAN, FATIMAH KHALIFAH MOHAMMAD; ALMADANI, MAHA BAHJAT (International Journal of Current Pharmaceutical Research, 2020)
Hand hygiene (HH) is the single most important procedure that can be followed by healthcare workers (HCWs) to reduce the risk of spreading healthcare-associated infections. The irritating contact dermatitis (ICD) that occurs due to the rehashed presentation of HH products and technique is one reason often referred to for resistance. HH is the most vital method that can be followed by HCWs to reduce the possibility of spreading of infection in human being, followed by50% of HCWs. Limited researches are published related to different features of irritant contact disorders among HCWs. This study concentrates manly on the clinical application of irritant contact dermatitis on hands and its diagnosis based on an extensive research review process. It can be concluded from this review that by proper adherence and compliance to necessary HH techniques lead to skin damage and higher pathogen load. Therefore, it is important that HCWs should appreciate this concept and are given methods or tactics of expertise to avoid skin irritation and damage. Inability to provide proper policies, practices and guidelines to these workers may lead to adherence in case of an ICD appearance.